2016
DOI: 10.1002/14651858.cd006439.pub4
|View full text |Cite
|
Sign up to set email alerts
|

Chromoscopy versus conventional endoscopy for the detection of polyps in the colon and rectum

Abstract: There is strong evidence that chromoscopy enhances the detection of neoplasia in the colon and rectum. People with neoplastic polyps, particularly those with multiple polyps, are at increased risk of developing colorectal cancer. Such lesions, which presumably would be missed with conventional colonoscopy, could contribute to the interval cancer numbers on any surveillance programme.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
1
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(47 citation statements)
references
References 62 publications
0
41
1
5
Order By: Relevance
“…Однако, по данным Кокрей-новского обзора [10], проанализировавшего пять рандомизированных клинических исследований (РКИ), оценившего роль прицельной хромоско-пии в выявлении колоректальных поражений при отсутствии полипоза и колита, было показано, что выполнение тотальной хромоскопии значительно увеличило число пациентов с, как минимум, од-ним выявленным полипом (соотношение шансов По данным японского эндоскопического фо-рума, прошедшего в 2014 г. в Отару (Хоккайдо), хромоскопия позволяет обеспечить большее об-наружение небольших полипов, плоских пораже-ний, аденом и количество пациентов, имеющих по крайней мере одну аденому, при этом в осно-вном в правой половине ТК [25]. По данным по-следнего Кокрейновского обзора [11], существу-ют убедительные доказательства того, что хромос-копия улучшает обнаружение неоплазии в толстом кишечнике. При этом частота обнаружения малых полипов увеличивается примерно на 90 % с помо-щью хромоскопии, а частота обнаружения малых полипов, способных перейти в рак, примерно на 30 %.…”
Section: оригінальні дослідженняunclassified
“…Однако, по данным Кокрей-новского обзора [10], проанализировавшего пять рандомизированных клинических исследований (РКИ), оценившего роль прицельной хромоско-пии в выявлении колоректальных поражений при отсутствии полипоза и колита, было показано, что выполнение тотальной хромоскопии значительно увеличило число пациентов с, как минимум, од-ним выявленным полипом (соотношение шансов По данным японского эндоскопического фо-рума, прошедшего в 2014 г. в Отару (Хоккайдо), хромоскопия позволяет обеспечить большее об-наружение небольших полипов, плоских пораже-ний, аденом и количество пациентов, имеющих по крайней мере одну аденому, при этом в осно-вном в правой половине ТК [25]. По данным по-следнего Кокрейновского обзора [11], существу-ют убедительные доказательства того, что хромос-копия улучшает обнаружение неоплазии в толстом кишечнике. При этом частота обнаружения малых полипов увеличивается примерно на 90 % с помо-щью хромоскопии, а частота обнаружения малых полипов, способных перейти в рак, примерно на 30 %.…”
Section: оригінальні дослідженняunclassified
“…78,128 A systematic review of five studies indicates similar conclusions. 129 The time taken to administer dye-spray could be reduced by a colonic release formulation of methylene blue (Methylene Blue MMX; MMX Cosmo Technologies, Ireland), which has proof of concept in a preliminary trial 130 , but awaits validation.…”
Section: Retroflexionmentioning
confidence: 99%
“…A Cochrane meta-analysis concluded that chromoendoscopy with indigo carmine enhances the detection of neoplastic polyps [6]. The review examined five randomized controlled trials, excluding polyposis or colitis patients [7][8][9][10][11], representing 1059 patients.…”
Section: Pan-chromoendoscopy For Lesion Detection In a Surveillance Pmentioning
confidence: 99%